THE STATISTICAL COMPARISON OF RADON CONCENTRATIONS IN THE STATIONS ON THE SIVRICE FAULT ZONE - Bal, Sultan Sahin; Dogru, Mahmut; Ozbey, Fahrettin; Aksoy, Ercan (Parlar Scientific Publications (P S P), 2020)
In this study, the radon concentration levels of the four different stations on the Sivrice Fault Zone are determined by Nuclear Spectroscopy with Alpha-Meter 611 sensors. Also the relation between the radon concentration values of the stations has been investigated via ANOVA and other statistical variables (mean, standard deviation, correlation coefficients). The mean radon concentration values of the stations are found as 66.45 kBq/m(3) in the Gezin, 227.13 kBq/m(3) in the Sogukpinar, 103.94 kBq/m(3) in the Keisebayir and 24.47 kBq/m(3) in the Sivrice.
Keywords: Radon; Statistic; Sivrice fault zone